The genus Aphaniosoma Becker, 1903 (Diptera: Chyromyidae) in the Eastern Mediterranean and Middle East, with descriptions of new species - Ebejer, Martin J. (European Journal of Taxonomy, 2023)
The species of Aphaniosoma Becker, 1903 described from Egypt by Collin in 1949 are reviewed and lectotypes designated for Aphaniosoma creperum Collin, 1949, A. fissum Collin, 1949, A. lamellatum Collin, 1949 and A. sodalis Collin, 1949. All species known from the eastern Mediterranean and the Middle East are reviewed, with annotations, distributions and a key to species. The following 19 species are described as new and illustrated: A. acitergum sp. nov., A. aegyptium sp. nov., A. angulitergum sp. nov., A. captiosum sp. nov., A. cristatum sp. nov., A. curvistylus sp. nov., A. daedalum sp. nov., A. denticulosum sp. nov., A. flavipyga sp. nov., A. freidbergi sp. nov., A. interispina sp. nov., A. kravchenkoi sp. nov., A. longilingua sp. nov., A. lucidum sp. nov., A. meltseri sp. nov., A. miricercus sp. nov., A. palestinense sp. nov., A. praeditum sp. nov. and A. yaromi sp. nov. Biology and ecology are commented upon.